Effect of Oxygen Tension, Mn(II) Concentration, and Temperature on the Microbially Catalyzed Mn(II) Oxidation Rate in a Marine Fjord - Tebo, Bradley M. (1985)
We present evidence that the oxidation of Mn(II) in a zone above the O(2)/H(2)S interface in the water column of Saanich Inlet, British Columbia, Canada, is microbially catalyzed. We measured the uptake of (54)Mn(II) in water samples under in situ conditions of pH and temperature and in the presence and absence of oxygen. Experiments in the absence of oxygen provided a measure of the exchange of the tracer between the dissolved and solid pools of Mn(II); we interpret the difference between experiments in the presence and absence of oxygen to be a measure of Mn(II) oxidation. Using this method we examined the effect of oxygen tension, Mn(II) concentration, and temperature on the initial in situ Mn(II) oxidation rate (V(0)). Mn(II) oxidation was almost twice as fast under conditions of 67% air saturation (V(0)=5.5 nM h(−1)) as with the in situ concentration of 15 μM (5% air saturation; V(0)=3.1 nM h(−1)). Additions of ca. 18 μM Mn(II) completely inhibited all Mn(II) oxidation at three different depths in the oxidizing zone, and there was a temperature optimum for Mn(II) oxidation of around 20°C. These results are consistent with biologically mediated Mn(II) oxidation and indicate that the rate is limited by both oxygen and the concentration of microbial binding sites in this environment.